Local government debt: an application to the Spanish case - David Cantarero; Marta Pascual; Roberto Fernandez; María A. García-Vali\~nas (European Regional Science Association (ERSA), 2004)
For the last years, Europe has been subject to fiscal austerity in order to satisfy the Maastrich criteria. In this way, Spanish municipalities have been affected by new regulations and local government structure has changed. This paper is focused on the main factors that explain local government debt. In particular, budgetary information of a group of Spanish municipalities is used (1990-2000). Econometric analysis of cross section and panel data are presented. Key words:Fiscal Federalism, Local Government, debt, decentralization.
Keywords: 330; Fiscal Federalism; Local Government; debt; decentralization